Conveyor belt structure and mode of operation in mines - Ravshanov Zavqiddin Yahyo oʻgʻli; O‘telbayev Azizbek Alisher o‘g‘li; O‘razmatov Jonibek Ikromboy o‘g‘li; Zaytova Madina Nazarbay qizi; Kulmuratova Aliya Janabay qizi (Genius Journals, 2022)
The paper discusses the results of a study carried out to determine the thermal condition of a conveyor power unit using a thermal imaging camera. The tests covered conveyors in the main haulage system carrying coal from a longwall. The measurements were taken with a thermal imaging diagnostic method which measures infrared radiation emitted by an object. This technology provides a means of assessing the imminence and severity of a possible failure or damage. The method is a non-contact measuring technique and offers great advantages in an underground mine. The thermograms were analysed by comparing the temperature distribution. An analysis of the operating time of the conveyors was also carried out and the causes of the thermal condition were determined. The main purpose of the research was to detect changes in thermal state during the operation of a belt conveyor that could indicate failure and permit early maintenance and eliminate the chance of a fire. The article also discusses the construction and principle of operation of a thermal imaging camera. The findings obtained from the research analysis on determining the thermal condition of the conveyor drive unit are a valuable source of information for the mine’s maintenance service
Keywords: Thermal imaging; belt conveyor; diagnostics; mechanical failure